Effects of flow modification and forest disturbance on streamflow across Colorado - Eurich, Abigail M., author; Kampf, Stephanie K., advisor; Bhaskar, Aditi, committee member; Evangelista, Paul, committee member (Colorado State University. Libraries, 2020)
Human activities alter streamflow around the world. In Colorado, flow modifications, land use change, and forest disturbances all modify streamflow, but the relative magnitudes of these effects are not well-quantified. This study examined how streamflow quantity across Colorado has been affected by three classes of change: (1) flow modifications from reservoirs and diversions, (2) urbanization, and (3) forest disturbance. The goal of this work was to identify the magnitude of streamflow alterations from these different types of stressors to understand the sensitivity of the state's streams to future changes, both natural and anthropogenic. A total of 215 watersheds were used to analyze effects of flow modifications and urbanization, and 71 of these watersheds were analyzed for effects of forest disturbance. Flow modifications and land use change have altered 85% of the gaged streams in this study. Of the stressors studied, the largest effects are from transbasin diversions, which reduce flow by an average of 20% in watersheds with diversions out of the watershed and increase flow by an average of 221% in watersheds with diversions importing water from another basin. Across all types of watersheds, the gaged streams in the Plains and Southwest regions of the state are most altered, and those in the Rio Grande are the least altered. The lower elevation areas are experiencing the largest percent changes relative to their natural flow regime (average water imports = 38 mm, 875%); the reduction in flow from high elevation watersheds is large in magnitude as well, but it equates to a smaller percent of the expected flow (average water exports = -71 mm, -18%). Forest disturbance may increase or decrease streamflow depending on the characteristics of the watershed and the disturbance, but the magnitude of the impact remains within the natural variability of streamflow in similar watersheds. A significant change in streamflow was observed in 25% of watersheds affected by disturbance, mainly with increases in flow following beetle mortality and severe wildfire. Streamflow decreased following smaller wildfires and in watersheds with South- and West-facing dominant aspects. Overall, anthropogenic modifications to streamflow via diversions that move water between watersheds have the largest effect on mean annual streamflow, whereas streamflow changes from forest disturbance mostly remain within the range of natural variability.
Keywords: diversion; transbasin; disturbance; urban; hydrology